1987
DOI: 10.1252/jcej.20.295
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nozzle length on gas entrainment characteristics of vertical liquid jet.

Abstract: For a vertical plunging liquid jet system using nozzles which had various values of the length-to-diameter ratio LJDn, characteristics such as the bubble penetration depth Z and the gas entrainment rate Qg were studied experimentally in an air-water system. Whennozzles of an LJDnratio exceeding 15 were employed,the values of Z and Qg were confirmed to be almost independent of LJDn. Empirical correlations for predicting Z and Qg are also presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1988
1988
1999
1999

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…The volumetric mass transfer coefficient kLa, was obtained by analyzing the response curves and Eq. (16).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The volumetric mass transfer coefficient kLa, was obtained by analyzing the response curves and Eq. (16).…”
Section: Methodsmentioning
confidence: 99%
“…1987; Kumagai et ai. 1983;Ohkawa et al 1987b] and the penetration depth of the bubbles produced by a vertical jet [Ohkawa et ai. 1986a] have attracted attention.…”
Section: Introductionmentioning
confidence: 99%
“…The values of c 1 , c 2 , c 3 , and c 4 were found to be 10.5, 0.54, -0.56, and 1.39, respectively, for two inclined plunging jets and 5.5, 0.73, -0.26, and 1.11 respectively for one inclined plunging jet by given Ohkawa et al (1986). Ohkawa et al, (1987) studied the vertical water jets and suggested for the dimensionless bubble penetration depth, H p /d N , the following expression:…”
Section: Figure (210)mentioning
confidence: 88%
“…This second technique is involved in the devices used by Ciborowski and Bin (1972b), Ahmed (1974), Ohkawa et al (1987), Evans (1990) and Kusabiraki et al (1990a). However, each of the above-mentioned techniques has its own shortcomings.…”
Section: Figure (211)mentioning
confidence: 99%
See 1 more Smart Citation